Tantangan Pengembangan Mobil Listrik Menuju Transportasi Berkelanjutan di Indonesia - Regina, Dewi; Ulmi, Nur Mazhariya (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2023)
The aim of this study is to determine the challenges of developing an electric vehicle (EV) in Indonesia. An electric vehicle (EV) is one solution for reducing carbon emissions and the use of fossil fuels in order to create sustainable transportation. This study used comparative studies from various countries, including China, Norway, America, Singapore, Malaysia, and Indonesia, to examine issues related to EV implementation and challenges that may arise. The literature review method was used for the research. According to the study's findings, the implementation of the EV system faces a number of challenges, including: a) large amounts of capital are required for EV production; b) EV prices are higher than conventional cars; and c) charging infrastructure is still limited. Government support is required for EV implementation on both the supply and demand sides.